The patient experience with shared decision-making in lung cancer: A survey of patients, significant others or care givers - Laurie Gaspar (The Beryl Institute, 2018)
A survey (via SurveyMonkey) was sent to lung cancer patients, their caregivers or significant others asking about their experience in making difficult treatment decisions. Of the 198 respondents, 118 (69%) indicated that they had faced a difficult decision with respect to their lung cancer treatment. Of those, 73% indicated that they would have desired that the decision be made with their physician using a shared decision-making process, and 58% perceived that such a process had occurred. In addition, only 23% of respondents indicated that they had had the right amount of information when making the decision. Fortunately, only 9% of respondents expressed regret regarding the decision they ultimately made. A Patient Decision Aid (PDA) was made available to the respondents to view, and opinions were sought regarding the usefulness of this type of format for presenting information. This format was perceived as helpful, unsure if helpful, or not helpful by 62%, 36%, and 2% of respondents, respectively. In summary, the majority of lung cancer patients want to make difficult decisions using a shared decision-making process. The patient perception is that this is not occurring often enough. Even in this fairly well-educated group of respondents, many report that they are not sure that they have all the information necessary to make that difficult decision. Physicians may need help developing their communication and shared decision-making skills. Introducing PDAs into the oncology clinic may represent a way to present complex information and improve the patient experience.